2015
DOI: 10.1177/1077546315623147
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle axle identification using wavelet analysis of bridge global responses

Abstract: Bridge weigh-in-motion (BWIM) technique uses an instrumented bridge as a weighing scale to estimate vehicle weights. Traditional BWIM systems use axle detectors placed on the road surface to identify vehicle axles. However, the axle detectors have poor durability due to the direct exposure to the traffic. To resolve this issue, a free-of-axle-detector (FAD) algorithm, which eliminates the use of axle detectors, was proposed. As a further improvement to simplify the BWIM systems, the concept of nothing-on-road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…The results show that the wavelet techniques can help identify closely spaced axles within a tandem or tridem group which could not be directly identified from the FAD signal and reveal the potential of using the wavelet techniques to identify vehicle axles from the strain signal of weighing sensors. Yu et al (2015) proposed a vehicle axle identification method based on the wavelet transformation of the global signal. The numerical results showed that this method could provide accurate identification of vehicle axles using only the weighing sensors.…”
Section: Axle Detectionmentioning
confidence: 99%
“…The results show that the wavelet techniques can help identify closely spaced axles within a tandem or tridem group which could not be directly identified from the FAD signal and reveal the potential of using the wavelet techniques to identify vehicle axles from the strain signal of weighing sensors. Yu et al (2015) proposed a vehicle axle identification method based on the wavelet transformation of the global signal. The numerical results showed that this method could provide accurate identification of vehicle axles using only the weighing sensors.…”
Section: Axle Detectionmentioning
confidence: 99%
“…Furthermore, based on the electrical resistance, the strain sensor senses the vehicles by its deformation. When installed under a bridge deck, the signals of a strain sensor peaks when wheels pass over the observation section [ 14 , 15 ]. Wavelet analysis [ 16 ] is proposed to detect a moving vehicle, and furthermore, to recognize the axles as well as classify the vehicle type.…”
Section: Related Workmentioning
confidence: 99%
“…To better describe the accuracy of identification, the identification error (IE) is defined as (Yu et al, 2017) Identification error = P iden À P true P true 3 100% ð6Þ…”
Section: Numerical Examplementioning
confidence: 99%